Multisystem Mitochondrial Disease Associated With a Mare m.10000G>A Mitochondrial tRNAGly (MT-TG) Variant - Yang, Haiyan; Zhang, Victor Wei; Ai, Liang; Gan, Siyi; Wu, Liwen (Frontiers in Neurology, 2022)
Background: Mitochondrial diseases are clinically heterogeneous, can occur at any age and can manifest with a wide range of clinical symptoms. Mitochondrial diseases can involve any organ or tissue, characteristically involve multiple systems, typically affecting organs that are highly dependent on aerobic metabolism, and making a definitive molecular diagnosis of a mitochondrial disorder is challenging. Methods: Clinical data of the proband and his family members were gathered in a retrospective study. Whole-exome sequencing and full-length sequencing of the mitochondrial genome that was performed on peripheral blood, urine and oral mucosa cells were applied for genetic analysis. Results: In this study, we reported a childhood-onset mitochondrial phenotype of a 13-year-old patient. Analysis of the next generation sequencing data of the nuclear genome and the full-length sequencing of the mitochondrial genome revealed a rare m.10000G>A variant in MT-TG that was present at variable heteroplasmy levels across tissue types: 32.7% blood, 56.15% urinary epithelial cells, and 27.3% oral mucosa cells. No variant was found in peripheral blood of his mother and sister. There was no pathogenic mutation of nDNA was found. Conclusion: our results added evidence that the de novo m.10000G>A variation in the highly conserved sequence of MT-TG appears to suggest a childhood-onset mitochondrial phenotype of a 13-year-old patient, thus broaden the genotypic interpretation of mitochondrial DNA related disease.